Detection of Group D Avian Rotaviruses among Layer Poultry from Western India - Niture, G.S.; Karpe, A.G.; Prasad, Minakshi; Bhonsle, A.V.; Patil, S.V. (International Journal of Poultry Science, 2009)
Rotavirus is a major cause of gastroenteritis in infants and children worldwide and also in wide variety of mammalian and avian species. In the present study, 4 (7.84%) out of the 54 poultry faecal samples tested, were found positive by RNA-PAGE. The samples were of 60-65 weeks age layer poultry birds suffering from diarrhoea. All the PAGE positive samples resolved in to 11 segments with a migration pattern of 5:2:2:2 characteristic of group D avian rotavirus. All the positive samples were of short electropherotype in which segments 10th and 11th migrated very closely. Avian rotavirus samples subjected to VP4 and VP7 gene based RT-PCR did not amplified respective products. RNA-PAGE positive samples were further subjected to VP6 gene based RT-PCR amplification using specific primers. All the four positive samples yielded a specific product of 493 bp. The study reports first ever detection of Group D avian rotavirus in Western India.